A low willingness to pay in a duopoly a la Hotelling: The role of the public firm - Stefano Quarta (Economics and Econometrics Research Institute (EERI), 2019)
The purpose of this paper is to analyze the role of the public firm in a spatial duopoly model a la Hotelling in the case of a low willingness to pay. We find that the presence of a public firm has the well known regulatory function in a market with a relative high willingness to pay; it is irrelevant in a market with a medium level of the willingness to pay; the relevance is for a low willingness to pay, where it ensures the full market coverage (as a result of the standard welfare maximization); finally, if the willingness to pay is very low, the public firm ensures a higher, but not full, market coverage with respect to the pure private case. Finally, we find that, for a low willingness to pay, the presence of the public firm is not sufficient to guarantee the optimal market configuration, so that the efficient level of welfare.
Keywords: L13; C72; D71; 330; Mixed duopoly; full market coverage; low willingness to pay; efficient welfare